History and development direction of iterative upgrading of deep coalbed methane reservoir reconstruction technology：Taking the Daji Block in the eastern margin of the Ordos Basin as an example - Fengyin XU; Huaibin ZHEN; Shuguang LI; Feng WANG; Lei ZHANG; Yubin WANG; Weichu YU; Weiping ZHU; Borui XU; Yun YANG; Haifeng ZHAO; Kunsen BAI (Meitan kexue jishu)
In 2019, PetroChina’s Coalbed Methane (CBM) Company achieved a groundbreaking breakthrough in the profitable development of deep coalbed methane reservoirs. This was accomplished through technological innovation in reservoir stimulation for the deeply buried No. 8 coal seam in the Daji block, located on the eastern margin of the Ordos Basin, with burial depths exceeding 2 000 m. This success significantly accelerated the exploration and development of deep CBM across the country, marking the beginning of the most prosperous period in the history of China’s CBM industry. Over the past five years, practical experience has demonstrated that advancements and iterative upgrades in reservoir stimulation technologies are key pathways for driving the profitable development of deep CBM and achieving reserve growth and production increases. This paper systematically reviews the stages and iterative progress of reservoir stimulation technologies since the profitable development of deep CBM was realized. Four fracturing technologies—Volumetric acidizing, large-scale volumetric fracturing, ultra-large-scale volumetric fracturing, and integrated geological-engineering precision fracturing—are examined in terms of their implementation and effectiveness. Additionally, a brief analysis of the performance of corresponding fracturing fluid systems is provided.The technological progression evolved from pursuing matrix stimulation to achieving large-scale fracture networks, from maximizing stimulation volume to optimizing well-to-fracture network integration, and eventually to adopting innovative technologies and advanced concepts for reservoir stimulation. Practical application of finely tailored fracturing designs based on geological characteristics has yielded remarkable results.However, the paper identifies five key challenges and areas for improvement in deep coal reservoir stimulation: High water consumption and difficulties in managing flowback fluids during ultra-large-scale fracturing; The need for breakthroughs in intelligent fracturing technologies; Immaturity of collaborative fracturing methods; The urgent requirement to establish fracturing technology systems for deep, medium-to-low-rank coal seams; Incomplete functionality of fracturing fluids.To address these challenges, six development directions are proposed:① Advancing water-reducing fracturing techniques; ② Conducting research on fishbone horizontal wells combined with matrix acidizing for large-scale water-reduction and production enhancement; ③ Expanding the application of artificial intelligence in intelligent fracturing and post-fracturing evaluation; ④ Developing and implementing collaborative fracturing techniques to optimize well-to-fracture network integration; ⑤ Strengthening research and development and application of stimulation technologies for deep, medium-to-low-rank coal reservoirs; ⑥ Innovating new fracturing materials to further reduce costs, improve efficiency, and enhance recovery rates for deep CBM.